Identification of Determinant Socio-Economic Variables for the Success of Biodiversity Conservation - Salbiah Hanum Hasibuan; Arzyana Sunkar; Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Biodiversity conservation in national parks has not shown an expected result. Biological natural resources degradation is still on going and its almost entirely due to human activities. Some researchers have indicated that socio-economic aspect is significantly related with the success of conservation. However, the researches have not yet shown in detail, which variabels were related with the succes conservation variables and how significant were the relations. This research was intended to identify the socio-economic variable(s) that would successfully determine biodiversity conservation in national park. The research was conducted in Gunung Halimun Salak Nasional Park, Ujung Kulon National Park, and Gunung Ciremai National Park from July to October 2015 using direct observation, literature study, and interview methods involving 150 respondents, selected based on random sampling in several resorts in the three national parks. Data were analyzed using pearson correlation tests using SPSS PSAW statistic 18. The achievement of biodiversity conservation was determined by the decrease in the number of individual species, increase in the rate of encroachment, increase of illegal natural resource utilization, increase violation of regulation, positive interaction, and biodiversity utilization. Results showed that variables leading to the succesful biodiversity conservation were: 1) determinant variable to decrease in the number of species is religion & customary system; 2) determinant variables to increase in encroachment rate is age and distance; 3) determinant variable to increase illegal natural resource utilization is land ownership; 4) determinant variable to increase violation of regulation is family dependant; 5) determinant variables to positive interaction is age and distance; 6) determinant variable to biodiversity utilization is education.Keywords: biodiversity conservation, determinant variables, national park, socio-economic variables